Gastroenterological problems in the elderly - Lipiński, Michał; Rydzewska, Grażyna (Przewodnik Lekarza/Guide for GPs, 2007)
An increasing number of elderly people suffer from gastroenterological problems. The most common gastroenterological disorders in this category of patients include constipations, fecal incontinence and diverticular disease which can progress to diverticulitis. The author draws the attention to the specificity of symptoms which often remain vague and atypical, presents the diagnostics and recommended regimens of treatment of the abovementioned diseases. The importance of non-clinic and non-pharmacological methods in the therapy is also discussed. The article covers also the ethical issues involved in the prognosis and treatment of elderly patients.